The university as an organism towards a more effective management system in the University of the Philippines - De Guzman, Raul P. (1976)
The complex structure of the University as an agent of change and a growing organism requires it to utilize its resources in terms of leadership requirements, administrative management, and rewards system in the attainment of its goals and objectives. This paper makes proposals, focusing on the University of the Philippines, for the development of the three factors previously mentioned. These proposals are the recruitment of scholar-administrators and development-oriented leaders; the development of a management information system; and the maintenance of a proper balance between central and college administration. Added to these are the formulation and consistent implementation of policies and criteria for retention and selective promotion of personnel and provisions for more incentives and financial remunerations.
Keywords: Public administration -- Management; Universities and colleges -- Administration, 1965-1986